A new species of Gorogobius (Perciformes: Gobiidae) from Sao Tomé Islands - Kovačić, Marcelo; Schliewen, Ulrich K (Zootaxa, 2008)
Gorogobius stevcici sp. nov. is described from the São Tomé Islands, Gulf of Guinea. Although it exhibits the unique combination of characters of Gorogobius Miller, it differs from present generic diagnosis of that genus. Therefore, a revised generic diagnosis and description of Gorogobius is provided. The new species differs from its only congener, G. nigricintus, by (1) presence of pore β; (2) row g anteriorly ends more or less in front of row o; (3) transverse interorbital row p present; (4) snout with four median preorbital rows; (5) 37–41 vs. 29–33 longitudinal scale rows; (6) 22–24 vs. 18 predorsal scales; (7) 9 vs. 10–11 anal fin rays; (8) 17 vs. 18–20 pectoral fin rays; (9) coloration.